2001
DOI: 10.1002/hup.258
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of THC in fat and brain: resulting functional responses to marihuana smoking

Abstract: A pleasant sensory perception (PSP), the high of THC or of marihuana consumption, is a consistent functional response to this drug only manifested by man, and which occurs concurrently with an increased heart rate. However, it has not been possible to relate consistently magnitude and duration of these functional markers to THC plasma concentration, whatever the route of administration. A re-analysis of all the available clinical and experimental data reporting the pharmacokinetics and storage of THC in tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However, dysphoric reactions, including anxiety and panic, depression, paranoia and psychosis can also occur. Systemic effects include a dose-related tachycardia, vasodilation and postural hypotension [55][56][57][58][59].…”
Section: Neuroimaging Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dysphoric reactions, including anxiety and panic, depression, paranoia and psychosis can also occur. Systemic effects include a dose-related tachycardia, vasodilation and postural hypotension [55][56][57][58][59].…”
Section: Neuroimaging Findingsmentioning
confidence: 99%
“…THC is a lipid-soluble substance that is distributed heterogeneously within the brain, with its highest concentrations in neocortical, limbic, sensory and motor areas [55][56][57][58]. THC and other cannabinoids exert their effects by the interaction with specific cannabinoid receptors, which are distributed heterogeneously within the brain [59][60][61][62][63][64].…”
Section: Neuroimaging Findingsmentioning
confidence: 99%
“…14 C THC was measured in fat, brain and testis sampled at the same time. (Nahas, 2001) (Trudell, 1977). Resulting activation of phospholipases (PPL) and production of arachidonic acid (AA), arachidonyl ethanolamide (AEA) and eicosanoids.…”
Section: Thc and Induction Of Premature Apoptosis Of Spermatozoamentioning
confidence: 99%
“…We found very low nanomolar concentrations in blood serum of THCtreated mice, which might be a consequence of local THC storage within fat tissue, as cannabinoids are known to be very lipophilic. Indeed, several animal experiments have demonstrated that the instant uptake and unlimited storage of THC by neutral fat limits the molecular concentration of the drug present in plasma (Nahas et al, 1981;Nahas, 2001;McGilveray, 2005). The hypercholesterolemic ApoE -/ -mouse model is characterized by a strong accumulation of fat tissue, especially within the vessel wall.…”
Section: Cannabinoids and Atherogenesismentioning
confidence: 99%